A beginning exploration of text generation abilities in university students with a history of reading difficulties. (5th March 2019) - MacKay, Elizabeth J.; Larcohe, Annie; Parrila, Rauno; Deacon, S. Hélène
Abstract : There is a fundamental lack of understanding of how university students with a history of reading difficulties perform on various demanding literacy tasks. We compared the text generation skills, measured with timed summary writing and proofreading tasks, of university students with a history of reading difficulties to those of students with no such history. We further examined whether between‐group differences in text generation skills remained after controlling for transcription skills (spelling and handwriting fluency), word reading, and reading comprehension. Forty‐six university students with a history of reading difficulties were matched on age, gender, and non‐verbal intelligence to 46 students without this history. We found that the students with a history of reading difficulties performed poorer on both measures of text generation than students without this history. When differences in transcription skills, word reading, and reading comprehension were controlled, we found that only differences in timed summary writing remained significant. These results suggest that students with a history of reading difficulties experience challenges with specific aspects of text generation that are beyond what one would expect from their difficulties with transcription and word reading. We suggest that, if not addressed, text generation deficits are likely to create obstacles for academic success.